Aesthetical Form and Educative Messages of Illustration Image of Bukan Sekadar Air Mata (Not Merely Tears) Short Story by Abdullah Ibnu Thalhah (Catharsis, 2022)
Some people still underestimate art. Art is a keyword in all fields. For example, the design of advertisements on industrial products that seek to touch the needs of emotion and imagination of its consumers. A short story illustration is a part of a work of art that illustrates a short story narrative text. There is an expression stated that the short story text acts as a Master, while the short story illustration acts as a servant who is obedient to his Master. It means that the illustrations for short stories are only seen as decoration. This study aims to describe and analyze the aesthetic form and educational message of the illustrated Bukan Sekadar Air Mata (Not Merely Tears) short story by Ibnu Talhah. The research method used qualitative research with a case study design. The data collection used observation, interviews, and documentation. According to Miles and Huberman, this study used data analysis techniques: data reduction, data presentation, and drawing conclusions. This study's results indicate three stages in analyzing the visuals in the illustrated short stories, including description, formal analysis, and interpretation. The embodiment of the aesthetic form of the illustration for the Bukan Sekadar Air Mata short story by Ibnu Talhah is surreal, with black and white colour domination. Each object drawn has a hidden meaning in it. In the illustration, the Bukan Sekadar Air Mata short story contains educational messages, including religious, moral, social, and cultural values. The significance of this research is educating the readers that short story illustrations cannot be seen as decoration only because it visualizes the narrative texts that contain meaning and educational messages, which can be used as a medium for public awareness regarding phenomena in society.